A chitosan-based fluorescent hydrogel for selective detection of Fe2+ ions in gel-to-sol mode and turn-off fluorescence mode. Issue 37 (11th September 2019) - Fan, Kaiqi; Wang, Xiaobo; Yu, Shuyan; Han, Guanglu; Xu, Die; Zhou, Liming; Song, Jian
Abstract : A novel chitosan-based fluorescent hydrogel has been synthesized by chemically bonding terpyridine-bearing aldehydes onto chitosan via an acid condensation reaction. Abstract : A novel chitosan-based fluorescent hydrogel has been synthesized by chemically bonding terpyridine-bearing aldehydes onto chitosan via an acid condensation reaction. More interestingly, such a hydrogel works as a dual-mode chemosensor for selective, rapid, gel-to-sol, and turn-off fluorescence sensing of Fe 2+ ions. In the gel-to-sol mode, the detection limit for Fe 2+ ions is 0.28 ppm, and in the turn-off fluorescence mode, the detection limit is 3.8 ppb. Such hydrogel-based fluorescent chemosensors are potentially suitable for the monitoring of Fe 2+ in biological and environmental applications.